(untitled) (Zien Journal of Social Sciences and Humanities, 2024)
In this article, the development of the agricultural sector on the basis of ecological requirements, the possibilities of meeting the growing needs of the population for food products, minimizing the level of environmental degradation associated with certain methods of agricultural management, and solving the problem of poverty in rural areas. explained about.